Videolaryngoscope-Aided Electrode Placement for Lower Cranial Nerve Monitoring in a Child with Tonsillar Enlargement - Thakkar, Keta; Singh, Georgene; Babu, K. S. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Intraoperative neuromonitoring for tumor resection near brain stem consists of monitoring the lower cranial nerves (CNs) and motor evoked potentials to check for integrity of CN and corticospinal pathway. Usually CN mapping of CN VII (orbicularis oris/oculi and frontalis bilaterally), CN IX, CN X (posterior pharyngeal wall and soft palate bilaterally, vocal cords), CN XI (sternomastoid bilaterally), and CN XII (tongue bilaterally) is done. An intraoral pathology such as tonsillar enlargement especially in pediatric patients can pose a challenge to placement of the electrodes for CN monitoring. Videolaryngoscope will aid in better visualization and safe and precise placement of electrodes in the posterior pharyngeal wall, soft palate, vocal cords, and tongue. Thus, integration of different technologies aims to provide a safer and scientifically sound anesthetic technique and improves the outcome even in challenging situations.
Keywords: midline suboccipital craniotomy; intraoperative cranial nerve monitoring; videolaryngoscope; tonsillar enlargement